Punishment for Zina Muḥṣān Offenders in Aceh Qanun No. 6 of 2014 in the Perspective of Fiqh al-Siyāsah - Fahmi, Mutiara; Hasan, Nurhayati Ali; Usman, Iskandar; Abdullah, Amiruddin; Hanafiyah, Muhibuddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This paper attempts to answer the issue of punishment for zina muḥṣān offenders in Aceh Qanun No. 6 of 2014 from the perspective of fiqh al-siyāsah and the ways the law is implemented in closed spaces such as prisons per the Governor Regulation No. 5 of the 2018. This study is a legal study with a Islamic politic approach (fiqh al-siyāsah) with a literature study data collection method. The polemic of the implementation of the Qanun Jinayah (criminal regional bylaws) in Aceh not only receives attention from outside such as human rights and non-governmental organization activists, but also from among Islamic academics or Acehnese ulemas. One of the most discussed topics is related to ‘uqūbah (punishment) for fornicators that does not distinguish between muḥṣān (married) and ghayr muḥṣān (unmarried) fornicators as is the case in classical fiqh (Islamic jurisprudence) literature. Qanun Jinayah does not at all separate between muḥṣān and ghayr muḥṣān fornicators, unlike the provisions of Islamic law which prescribe a hundred lashes for ghayr muḥṣān fornicators and stoning to death for muḥṣān fornicators. This indicates that those who commit zina in Aceh, whether married or unmarried, are punished with the same severity, which is 100 (one hundred) lashes. Further, the issue of changing the place of the flogging execution from public to prison in accordance with Aceh Governor Regulation No. 5 of 2018 concerning the implementation of the jināyah (criminal) procedural law is also worth to study from the point of view of fiqh al-siyāsah (Islamic politics) and legislation.